Pengaruh Pembayaran Non Tunai dan Aplikasi Belanja Online terhadap Perilaku Manajemen Keuangan Studi Kasus Mahasiswa Program Sarjana Program Studi Manajemen Universitas Islam Kadiri - Sukma, Dyah Ayu; Arisyahidin, Arisyahidin; Hastuti, Sri Wahyuni Mega (Universitas Islam Kadiri, 2023)
Digital transformation in the financial sector has fundamentally reshaped the way individuals, especially university students, manage their personal finances. The widespread use of cashless payment systems such as digital wallets (e-wallets), QRIS, and mobile banking, along with easy access to online shopping platforms like Shopee, Tokopedia, and Lazada, has not only simplified transactions but also significantly influenced consumption patterns. This study aims to examine the influence of cashless payments and online shopping applications on the financial management behavior of students. The research adopts a literature review method by analyzing various relevant academic journals, theses, and scholarly books. Findings reveal that while digital transaction tools enhance efficiency in financial management, they also pose risks of impulsive spending if not accompanied by adequate financial literacy and self-control. Students often exhibit consumer behavior driven by digital promotions, installment facilities, and credit features such as paylater. Therefore, financial literacy and the development of sound financial management habits are crucial to building financially resilient and literate student communities. The study recommends that higher education institutions take a more active role in integrating financial literacy into the academic curriculum and fostering awareness among students to make wise financial decisions in the digital era.)